Pengaruh Dukungan Keluarga dan Efek Samping Kemoterapi terhadap Kualitas Hidup Pasien Kanker Payudara Diruang Kemoterapi di RSUD Karawang - Saroni, Muhammad Nur; Fitriani, Elfira Sri (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Cancer, also known as malignant tumor disease, is a non-malignant condition diagnosed by the presence of abnormal malignant cells or tissues, which can spread to other areas of the patient's tubules. Cancer cells have a malignant form that can attack and damage the function of surrounding tissues. The spread (metastasis) of cancer cells can be caused by lymph or blood vessels. to determine the Effect of Family Support and Side Effects of Chemotherapy on the Quality of Life of Breast Cancer Patients Undergoing Chemotherapy in the Chemotherapy Room at Karawang Hospital. The design of this study is a quantitative analytical study with a cross- sectional design. Sampling in thisstudy was determined by total sampling. Total sampling is a sampling technique where the number of samples is the same as the population. The reason for taking total sampling is because the population is less than 100 so that theentire population is used as a research sample. The type of bivariate analysis uses the Chi Square statistical test. The Chi Square test is included in non-parametric statistics. From the Chi-Square results, the P-Value data was obtained 0.046 (<0.05), meaning that there is a significant relationship between the side effects of chemotherapy and the quality of life of breast cancer patients undergoing chemotherapy in the chemotherapy room at Karawang Hospital and from the Chis-square test results, the p- value was obtained 0.047 (<0.05), meaning that there is a significant relationship between Family Support and the quality of life of breast cancer patients undergoing chemotherapy in the chemotherapy room at Karawang Hospital. From the results obtained, one of the efforts to achieve a good quality of life in breast cancer patients is not only couples who provide motivation, but the support of the extendedfamily and the community environment plays a very important role in increasing patient motivation in undergoing chemotherapy Keywords: Family Support, Side Effects of Chemotherapy, Patient Quality of Life, Breast Cancer  ABSTRAK Penyakit kanker, juga dikenal sebagai penyakit tumor ganas, adalah kondisi non-ganas yang didiagnosis dengan adanya sel atau jaringan berwarna ganas yang menyimpang, yang dapat menyebar ke area lain dari tubulus pasien. Sel kanker memiliki bentuk ganas yang dapat menyerang dan merusak fungsi jaringan di sekitarnya. Penyebaran (metastasis) sel kanker bisa disebabkan oleh pembuluh getah bening atau darah. Mengetahui Pengaruh Dukungan Keluarga dan Efek Samping Kemoterapi terhadap Kualitas Hidup Pasien Kanker Payudara Yang Menjalani Kemoterapi Diruang Kemoterapi RSUD Karawang. Desain penelitian ini merupakan penelitian analitik kuantitatif dengan rancangancross sectional. Pengambilan sampel pada penelitian ini ditentukan dengan cara total sampling. Total sampling adalahTeknik pengambilan sampel Dimana jumlah sampel sama dengan populasi Alasan mengambil total sampling karena jumlah populasi kurang dari 100 sehingga seluruh populasi dijadikan sampel penelitian semuanya. Jenis analisis bivariat menggunakan uji Uji statistik Chi Square. Uji Chi Square termasuk kedalam statistik non-parametrik. Darihasil Chi-Square diperoleh data P-Value 0,046 (< 0,05), Artinya ada hubungan yang signifikan antara Efek samping kemoterapi dengan kualitas hidup pasien kanker payudara yang menjalani kemoterapi diruang kemoterapi RSUDKarawang dan Dari Hasil Uji Chis-square diperoleh p-value 0,047 (< 0,05), Artinya ada hubungan yang signifikanDukungan Keluarga dengan kualitas hidup pasien kanker payudara yang menjalani kemoterapi diruang kemoterapi RSUD Karawang. Dari hasil yang didapat Salah satu upaya mencapai kualitas hidup yang baik pada pasien kanker payudara tidak hanya pasangan saja yang memberikan motivasi namun dukungan keluarga besar dan lingkungan masyarakat sangat berperan penting untuk meningkatkan motivasi pasien dalam menjalani kemoterapi. Kata Kunci: Dukungan Keluarga, Efek Samping Kemotrapi, Kualitas Hidup Pasien, Kanker Payudara